Synthesis and Assembly of Hepatitis B Virus-Like Particles in a Pichia pastoris Cell-Free System - Spice, Alex J.; Aw, Rochelle; Bracewell, Daniel G.; Polizzi, Karen M. (Frontiers in Bioengineering and Biotechnology, 2020)
Virus-like particles (VLPs) are supramolecular protein assemblies with the potential for unique and exciting applications in synthetic biology and medicine. Despite the attention VLPs have gained thus far, considerable limitations still persist in their production. Poorly scalable manufacturing technologies and inconsistent product architectures continue to restrict the full potential of VLPs. Cell-free protein synthesis (CFPS) offers an alternative approach to VLP production and has already proven to be successful, albeit using extracts from a limited number of organisms. Using a recently developed Pichia pastoris-based CFPS system, we have demonstrated the production of the model Hepatitis B core antigen VLP as a proof-of-concept. The VLPs produced in the CFPS system were found to have comparable characteristics to those previously produced in vivo and in vitro. Additionally, we have developed a facile and rapid synthesis, assembly and purification methodology that could be applied as a rapid prototyping platform for vaccine development or synthetic biology applications. Overall the CFPS methodology allows far greater throughput, which will expedite the screening of optimal assembly conditions for more robust and stable VLPs. This approach could therefore support the characterization of larger sample sets to improve vaccine development efficiency.